Cognitive Representation of Spontaneous Motion in a Second Language: An Exploration of Chinese Learners of English - Ji, Yinglin (Frontiers in Psychology, 2019)
This study tests whether Chinese learners of English can reconstruct their cognitive pattern in the direction of the target system when judging the similarity between spontaneous motion screens in a match–to–sample task. English main verbs encode Manner of motion only, while Chinese verb compounds express Manner and Path simultaneously. Chinese monolinguals are thus predicted to develop a motion cognition pattern highlighting both Manner and Path salience whereas English monolinguals are more likely to be Manner-oriented. Our research findings are twofold. First, when assessed by the explicit measure of selection strategies (i.e., either Manner–match or Path-match), both monolingual and L2 learners show a general preference for the Path–match. However, when gauged by the implicit measure of processing speed (i.e., reaction time), Chinese monolinguals reacted significantly quicker than their English counterparts, particularly in making Path-matched judgments. Further, the L2 English learners across proficiencies responded significantly more slowly than their monolingual counterparts even at an advanced stage of acquisition, suggesting that the process of conceptual reconstructing, as demonstrated in our experiment, can be cognitively demanding and needs a longer period of time to complete. These findings are generally consistent with a weak version of the linguistic relativity hypothesis.